Nutrition Considerations for Burn Patients: Optimizing Recovery and Healing - Beth A. Shields; Asia M. Nakakura (MDPI AG, 2023)
The hypermetabolic and hypercatabolic responses to severe burns put nutrition support at the forefront of treatments. When left untreated, severe weight loss, increased infection, and wound healing failure can occur. Enteral nutrition is the primary method of nutrition support in such patients. Meeting caloric needs and a positive nitrogen balance are short-term goals of nutrition support, with long-term goals of minimizing lean body mass loss and maximizing wound healing. High-carbohydrate and low-fat nutrition received evidence from randomized controlled trials of aiding in decreasing pneumonia rates and was found to promote positive nitrogen balance, which lipids do not do. We go through the macronutrient and micronutrient needs of the burn patient as well as techniques for meeting these needs in the modern intensive care unit, with some discussion of alterations in these techniques that are required in the austere environment.